Test and evaluation of aircraft avionics and weapon systems - McShea, Robert E. (Raleigh, NC SciTech Publishing, 2010)
The book reviews developments in the following fields: avionics; time, space, and position information; digital data busses; data reduction; data analysis; MIL-STD-1553; communications flight test; navigation systems; avionics civil certifications; electro-optical systems; infrared systems; radio detection; ranging; radar; electronic warfare; and weapons integration.
Electronic reproduction.
Keywords: Avionics -- Testing; Airplanes, Military -- Armament -- Testing; Airplanes -- Testing; Electronics in military engineering; Electrooptical devices; Infrared detectors; Electronic books